Proclaiming the peacemaker : the Malaysian church as an agent of reconciliation in a multicultural society - Rowan, Peter (Director of OMF International (UK)) (Regnum studies in mission., 2012)
"This book looks at the role of the church as a reconciling agent, arguing that a reconciling presence within a divided society necessitates an ethos of peacemaking. With a combination of theological, historical and sociological perspectives, Rowan sets out to demonstrate that being an agent of reconciliation is linked to our effectiveness in bearing witness to an identity given by Christ."--Back cover.